Energy futures price bubbles and asset co-movements with crude palm oil futures: through the lenses of geopolitical events and speculation - Abd Halim Ahmad; Airil Khalid; Siti Nurazira Mohd Daud; Zainudin Arsad; Mohammad Ashraful Mobin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The important role played by energy markets has concerned investors regarding the market’s behaviour and interconnections when seeking asset diversification strategies, which has become critical in financial analysis. This study aimed to identify price bubbles in energy futures markets and asset co-movements with the crude palm oil futures market (FCPO). This study utilised five futures indices from January 2, 2001, to October 30, 2020. Three methods were employed to explain the behaviour of the energy futures markets: The Generalized Supremum Augmented Dickey-Fuller (GSADF) test, the wavelet power spectrum technique and the wavelet coherence method. The findings from the GSADF test revealed that all energy future markets indicated the presence of asset bubbles, which were influenced by geopolitical events and speculation. The study also demonstrated the presence of periods of high volatility across multiple horizons, which occasionally occurred around the same period as explosive price behaviour. The results of the wavelet coherence method showed that the FCPO market had high co-movement with the Brent crude oil (BRENT) and heating oil (HOIL) markets and, to a lesser extent, with the natural gas (NGAS) and light sweet crude oil (WTI) markets. By linking the GSADF and wavelet approaches, the present study showed how energy price bubbles, their volatility, and co-movements with the FCPO market were related in the presence of geopolitical events and speculation. The present study's findings have suggested strategies regulators and investors can use to manage investment risk and portfolio diversification.